2017
DOI: 10.1590/1983-21252017v30n105rc
|View full text |Cite
|
Sign up to set email alerts
|

Production, Decomposition and Chemical Characteristics of Banana Litterfall

Abstract: -The characterization of litterfall in forest and agroforest systems is important to better understand the cycling of nutrients, however, few studies on litterfall of fruit trees, such as banana, are found. Therefore, the objective of this work was assess the production and decomposition and chemically characterize the litterfall of banana genotypes cropped in a dystrophic typical Red-Yellow Latossol, with weak A horizon, medium texture in a hypo-xerophytic Caatinga in the Southwest of Bahia, Brazil. A complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Unlike peach palm, the banana tree had a slow decomposition. Brito et al (2017) observed a slow decomposition of Japira banana litter, with a t1/2 of 236 days in an irrigated system, corroborating the results of the first and third evaluations, with strong recalcitrance and without adjustment of the equations. However, it was slower than in the second evaluation of the present study with t1/2 at 108 days, a fact explained by the lower C/N ratio (48/1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unlike peach palm, the banana tree had a slow decomposition. Brito et al (2017) observed a slow decomposition of Japira banana litter, with a t1/2 of 236 days in an irrigated system, corroborating the results of the first and third evaluations, with strong recalcitrance and without adjustment of the equations. However, it was slower than in the second evaluation of the present study with t1/2 at 108 days, a fact explained by the lower C/N ratio (48/1).…”
Section: Discussionsupporting
confidence: 81%
“…However, it is not possible to establish a relationship with the phenological stages of coffee, because the harvest is not concentrated on a date. In the evaluation started in March, DM-BAN t1/2 was only reached from K at 92.3 days, indicating a slow decomposition according to (Brito et al, 2017). Unlike banana residues, in the three evaluations of the DM-PP, the remaining N at 150 days were 20.6%, 23.8% and 21.5%, indicating fast decomposition, although slower than that observed by Pereira et al (2015) with 99.4% of the N released at 112 days with crushed and buried leaves.This rapid release of nutrients after each harvest, points to a favorable effect of DM-PP.…”
Section: Discussionmentioning
confidence: 94%
“…While the nutrient requirements of banana crops are generally assessed from yield potential, nutrient exportations through harvest, restitution of plant residues back to soil, nutrient leaching, soil erosion, plantation density, soil fertility, and root development [7,72,74], there are numerous controllable and uncontrollable growth factors and countless factor interactions impacting crop performance [75]. Features can be processed by ML models at a regional scale, where yield-impacting factors are averaged, or at a local scale, where site-specific factors are documented in a dataset.…”
Section: Can Local Diagnoses Sustain the Fertigated Banana Production System?mentioning
confidence: 99%
“…This has a practical implication in reducing the doses of fertilizers to be applied, as well as reducing production costs. In fertilization programs, it is important to consider the amount of nutrients immobilized in the banana dry matter that returns to the soil after harvest (OLIVEIRA et al, 2005;SILVA et al, 2015;BRITO et al, 2017). Hoffmann et al (2010), evaluating the accumulation of nutrients in six banana cultivars, found that the return of nutrients to the soil, such as Ca and Mg, may reach 95 and 89 %, respectively.…”
Section: Partitioning and Export Of Macronutrientsmentioning
confidence: 99%
“…Banana mats have high dry matter production and accumulate a large amount of nutrients in vegetative organs and fruits (NEVES et al, 1991;SOARES et al, 2008;HOFFMANN et al, 2010). Such high nutritional requirement is partly supplied by soil, fertilizer application and cycling of nutrients present in the plant residues produced during cultivation, which can be mineralized and subsequently absorbed by plants (TEIXEIRA et al, 2008;FAGERIA, 2009a;BRITO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%